2019
DOI: 10.1007/s10611-019-09846-5
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the crime drop: contributions to declining crime rates from youth cohorts since 2005

Abstract: Since the mid-90s there has been almost a 50% reduction in the volume of crime in England and Wales -a trend that has been mirrored in many Western countries (Greenberg Justice Quarterly, 31(1), 2014). Despite previous assumptions, for example, declining birth cohorts, it is proposed here that the decline in crime for the 1995-2005 period can largely be attributed to a doubling of the probability of a crime being 'proven' (cf Lloyd et al. 1994; MOJ, 2012;Taylor 2016). However, in the last decade these reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Nuorten omaisuusrikosten lasku on ollut varsin systemaattista 1990-luvun puolivälistä asti, kun taas väkivaltarikosten osalta määrä on lähtenyt laskuun 2010-luvulle tultaessa (Näsi & Tanskanen, 2017). Suomessa havaittu nuorisorikollisuuden kehitys onkin ollut samansuuntaista kuin muissa pohjoismaissa (Kivivuori & Bernburg, 2011) ja laajemmin kansainvälisesti (Fernández-Molina & Bartolomé Gutiérrez, 2020; van der Laan ym., 2021; Griffiths & Norris, 2020;McCarthy, 2020), mikä tukee kuvaa laaja-alaisesta kehityskulusta.…”
Section: Rikollisuuden Laskeva Trendi -'Crime Drop'unclassified
“…Nuorten omaisuusrikosten lasku on ollut varsin systemaattista 1990-luvun puolivälistä asti, kun taas väkivaltarikosten osalta määrä on lähtenyt laskuun 2010-luvulle tultaessa (Näsi & Tanskanen, 2017). Suomessa havaittu nuorisorikollisuuden kehitys onkin ollut samansuuntaista kuin muissa pohjoismaissa (Kivivuori & Bernburg, 2011) ja laajemmin kansainvälisesti (Fernández-Molina & Bartolomé Gutiérrez, 2020; van der Laan ym., 2021; Griffiths & Norris, 2020;McCarthy, 2020), mikä tukee kuvaa laaja-alaisesta kehityskulusta.…”
Section: Rikollisuuden Laskeva Trendi -'Crime Drop'unclassified
“…Braga and Weisburd (2020) also found support for the hypothesis that Place-based POP strategies reduced crime. Furthermore, a growing body of empirical studies has emerged concerning the role of period and cohort effects in the decline of crime (Dixon and Farrell 2020;Griffiths and Norris 2020;Kim et al 2016;Lu and Luo 2020;O'Brien 2019;O'Brien and Stockard 2009). For example, Kim et al (2016) found that cohort effects rather than period effects seemed to be a more important predictor in the decline of age-specific felony arrest rates in New York State.…”
Section: International Crime Drop In Retrospectmentioning
confidence: 99%
“…Moreover, there is good evidence from other fields of research that having a more pluralistic approach to understanding the nature of intergenerational transmission is of theoretical benefit. Added to which, recent major reductions in youth offending (Griffiths and Norris, 2020) may well have created a transformation in the patterns, nature and timing of offending between recent generations, which may lessen the value of a strict homotypic approach.…”
Section: Defining and Measuring Intergenerational Transmissionmentioning
confidence: 99%